2022
DOI: 10.1128/aem.00574-22
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Conjugates Derived from flg15, Pep13, and PIP1 That Are Active against Plant-Pathogenic Bacteria and Trigger Plant Defense Responses

Abstract: The consequences of plant pathogens on crop production together with the lack of effective and environmentally friendly pesticides evidence the need of new agents to control plant diseases. Antimicrobial and plant defense elicitor peptides have emerged as good candidates to tackle this problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 85 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…Interestingly, RIJK2 has been described to have other activities such as antibacterial and antibiofilm against Xff (Moll et al 2021 ). Regarding BP16 and FV7, they have been reported to display antibacterial activity against some Gram-negative bacteria, but not against X. fastidiosa (Badosa et al 2007 ; De La Fuente-Núñez et al 2012 ; Oliveras et al 2022 ). In addition, in previous studies, we identified peptide conjugates with interesting results and observed that the monomers present in their sequence as well as the order of the conjugation have an important influence on their activity as plant defense elicitors (Oliveras et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, RIJK2 has been described to have other activities such as antibacterial and antibiofilm against Xff (Moll et al 2021 ). Regarding BP16 and FV7, they have been reported to display antibacterial activity against some Gram-negative bacteria, but not against X. fastidiosa (Badosa et al 2007 ; De La Fuente-Núñez et al 2012 ; Oliveras et al 2022 ). In addition, in previous studies, we identified peptide conjugates with interesting results and observed that the monomers present in their sequence as well as the order of the conjugation have an important influence on their activity as plant defense elicitors (Oliveras et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding BP16 and FV7, they have been reported to display antibacterial activity against some Gram-negative bacteria, but not against X. fastidiosa (Badosa et al 2007 ; De La Fuente-Núñez et al 2012 ; Oliveras et al 2022 ). In addition, in previous studies, we identified peptide conjugates with interesting results and observed that the monomers present in their sequence as well as the order of the conjugation have an important influence on their activity as plant defense elicitors (Oliveras et al 2022 ). The most relevant peptide conjugates were BP100-flg15, flg15-BP100, and BP16-Pep13 , resulting from the conjugation of BP100 with flg15 and BP16 with Pep13 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our group we have recently reported the synthesis of peptide conjugates incorporating an antimicrobial sequence, derived from the lead peptide BP100 (KKLFKKILKYL-NH2), and a plant defense elicitor. These conjugates were screened for their antimicrobial activity against bacterial pathogens, their hemolytic activity, and their effect on plant defense gene expression [5].…”
Section: Introductionmentioning
confidence: 99%